Methods of Extraction: Maceration, Percolation and Decoction - Rachmat Hidayat; Patricia Wulandari (Eureka Herba Indonesia, 2021)
Today, natural medicines not only provide the primary healthcare needs for the majority of the population in developing countries but have attracted more and more attention in developed countries due to soaring healthcare costs and universal financial austerity. In the USA, approximately 49% of the population has tried natural medicines for the prevention and treatment of diseases. Chemicals known to have medicinal benefits are considered to be “active ingredients” or “active principles” of natural medicines. Natural products have provided the primary sources for new drug development.